SOSIALISASI PENERAPAN TEKNOLOGI IRIGASI TETES UNTUK BUDIDAYA TANAMAN SAYURAN DI KABUPATEN SEMARANG - Hetwisari, Tia; Herwindo, Wildan; Bumi, Ingerawi Sekaring; Patiroi, Andi; Aryani, Tri (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Getasan is a sub-district in Semarang Regency, Central Java, Indonesia which is located on the slopes of Mount Merbabu between Salatiga City and Magelang Regency. Batur is one of the villages in the Getasan Sub-District and is famous as one of the vegetable-producing areas in Semarang Regency. Utilization of water resources for vegetables in Batur Village currently still relies heavily on conventional irrigation which requires quite a lot of water. The implementation of a drip irrigation system is expected to be an alternative to save water use, especially during the dry season, so that vegetable production can continue throughout the year. The drip irrigation system technology implemented in Batur Village, Getasan Sub-District, Semarang Regency, needs to be known and understood by the public. Therefore, socialization as a transfer of knowledge about drip irrigation technology is needed, including community involvement in the process of installing/creating a pilot application of a drip irrigation system in their area. The results achieved in implementing this community service are the delivery of information regarding the benefits of drip irrigation technology, drip irrigation design, as well as operational and maintenance patterns of drip irrigation networks.